Analisis Kebutuhan Pengguna Aplikasi Ruangguru Menggunakan Metode Fuzzy Kano - Sarah Anindya Shofi; Aditya Rachmadi; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Ruangguru is application online tutoring that offers products which has the most complete solutions to problems that students from Indonesia face during their studies which is in the form of an. Based on the result of the interview and observation, the usage of Ruangguru affects the studying process in a positive manner. However, there were problems that occurred to the users of Ruangguru. The goal of this research is to analyze the Ruangguru application with methods concerning identifying, categorizing, and prioritizing requirements based on user satisfaction to which can decrease the problems experienced by users that may increase the overall quality of the Ruangguru application. A Fuzzy Kano method is utilized a quantitative and objective product development technique based on scores calculated from user satisfaction to raise a quality. This research uses purposive sampling, which targets a minimum of 97 respondents. The results are then categorized into 35 requirements which consists of: 26 requirements towards the study location, 6 requirements based on the digital bootcamp process, 3 requirements based on purchasing process. Out of 35 requirements defined as application features, 12 features are categorized as one-dimensional, 7 features that fall in the attractive quality attribute category, and 16 features fall under the indifferent quality attribute category. A priority list starting from the most important are feature "received explanation of the answer" in the one-dimensional category, "Finished the quiz" in the attractive quality category, "Viewed the tutor's explanation (in the form of text)" in the indifferent quality category.